Raw material availability, flaking quality, and hunter–gatherer technological decision making in northern Tierra del Fuego Island (southern South America) - Borrazzo, Karen Beatriz (2012)
The technological organization and lithic raw material procurement of Holocene hunter-gatherers have been topics of considerable interest in northern Tierra del Fuego Island. Ongoing archaeological investigations indicate that most of the rocks employed by native human populations came from secondary deposits of fluvio-glacial and marine origin. However, a primary geological source for two distinctive lithologies has been recently discovered near the Chorrillo Miraflores Valley (Tierra del Fuego, Chile). These raw materials became the focus of further research since one The technological organization and lithic raw material procurement of Holocene hunter-gatherers have been topics of considerable interest in northern Tierra del Fuego Island. Ongoing archaeological investigations indicate that most of the rocks employed by native human populations came from secondary deposits of fluvio-glacial and marine origin. However, a primary geological source for two distinctive lithologies has been recently discovered near the Chorrillo Miraflores Valley (Tierra del Fuego, Chile). These raw materials became the focus of further research since one of them (a silicified tuff) has been identified in several archaeological sites of Tierra del Fuego. Some of these sites are located more than a hundred kilometers away from the source. A regional survey of potential lithic sources along with petrographic and geochemical analyses confirmed that the silicified tuff is only available at Chorrillo Miraflores. Here we present the technological analysis of artifacts manufactured on Miraflores silicified tuff that were recovered from the Argentine portion of northern Tierra del Fuego composed of Espíritu Santo and San Sebastian Capes. The role of utilitarian currencies in the prehistoric use of this lithology is assessed through the application of the Metcalfe and Barlow (1992) field-processing model. The results show that this raw material may not have been exclusively selected for its flaking quality, although an alternative functional efficiency hypothesis is also introduced. Finally, its spatially restricted availability as well as unique macroscopic aspect suggests its selection and use may have been mainly influenced by social factors.